IMPLEMENTATION OF THE SEMONT APPLICATION AS A SIGNATURE-BASED INTRUSION DETECTION AND PREVENTION SYSTEM ON THE SMAN 1 RANCAEKEK COMPUTER NETWORK - Alwi Al Hadad; Hani Harafani (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
SMAN 1 Rancaekek is highly dependent on web applications that are vulnerable to injection attacks (SQL Injection, XSS, RCE, LFI), web defacement, and brute force, exacerbated by the absence of real-time monitoring, which has led to serious security incidents. This study aims to design and implement the Semont (Sentinel Monitoring) application as a signature-based Intrusion Detection and Prevention System (IDPS) to detect and prevent such cyber attacks, monitor network traffic on Port 80 (HTTP) and Port 443 (HTTPS), and generate comprehensive reports. The research method involved network system analysis and Semont design. The main contribution of this research is the development of a lightweight, efficient, and intuitive IDPS solution capable of protecting sensitive data and website visual integrity with minimal overhead. The analysis results show that Semont successfully detected and blocked 100% of simulated attacks, significantly changing the security posture of the SMAN 1 Rancaekek website from vulnerable to secure, supported by detailed logging and real-time notifications to Telegram. In conclusion, Semont proved to be highly effective in detecting and preventing common cyber attacks, meeting the need for proactive defense in educational environments, although the signature-based method is limited to zero-day attacks, which can be improved through the integration of anomaly detection in the future.